The role of immune checkpoint inhibitors in the first-line treatment for patients with advanced biliary tract cancer: a systematic review and meta-analysis of randomized trials - Vitale, Elsa; Rizzo, Alessandro; Maistrello, Lorenza; Nardulli, Patrizia; Talienti, Tiziana; Quaresmini, Davide; De Summa, Simona; Massafra, Raffaella; Silvestris, Nicola; Brunetti, Oronzo (Frontiers in Oncology, 2024)
Background: We performed a systematic review and meta-analysis to further explore the impact of the addition of immunotherapy to gemcitabine -cisplatin as first-line treatment for advanced BTC patients.Methods: Literature research was performed, Hazard Ratio values and their 95% confidence intervals were pull out. Heterogeneity among studies was assessed using the tau-squared estimator (𝜏 ). The total Cochrane Q test (Q) was also assessed. We assessed the overall survival rate, objective response rate and the progression-free survival in the selected studies.Results: 1,754 participants were included. Heterogeneity among the studies selected was found to be non-significant (P=0.78; tau 2 =0, I 2 = 0%). The model estimation results, and the Forest Plot suggested that the test for the overall effect were significant (Z=-3.51; P<0.01).The results of the current meta-analysis further confirm the role of immunecheckpoint inhibitors plus gemcitabine -cisplatin as the new standard first-line treatment for advanced BTC patients.